Worth of three doctor's degrees (On Bernardas Gailius "The Guerrilla War of 1944-1953 in the Historical, Political and Legal Culture of Contemporary Lithuania") - Lina Kaminskaitė-Jančiorienė (Lietuvos Istorijos Studijos)
-